Low-loss YIG thick films for microwave applications. Issue 4 (March 2019) - C, Mahender; T P, Sumangala; Ade, Ramesh; A, Saranya; Prasad, Shiva; Venkataramani, N.
Abstract: We report the fabrication, densification and characterization of polycrystalline free-standing yttrium iron garnet Y3 Fe5 O12 (YIG) thick films in this paper. The thick films were fabricated using a double doctor blade technique from co-precipitated nanocrystalline YIG powders. The sintering temperature of YIG thick films was varied from 1000 to 1400°C. A volume diffusion mechanism is seen to govern the densification process. A high relative density of 99% could be achieved in a YIG thick film, with a thickness of 80 µm, sintered at a relatively low temperature of 1300 °C. The magnetization value 1750 Oe, near to the YIG bulk magnetization value and an acceptable low ferromagnetic resonance (FMR) linewidth (∆H) of 80 Oe resulted in these high density YIG thick films with microwave device possibilities.